2005
DOI: 10.1521/aeap.2005.17.4.361
|View full text |Cite
|
Sign up to set email alerts
|

The Solaar HIV Prevention Program for Gay and Bisexual Latino Men: Using Social Marketing to Build Capacity for Service Provision and Evaluation

Abstract: Community-researcher partnerships can be powerful mechanisms to understand and effectively address health and social problems such as HIV/AIDS prevention. When the partnership is a positive, productive one, the combined expertise and energy of both parties result in a more effective program and a better evaluation of its effects. This article describes one such partnership and how a program challenge provided the opportunity for both partners to develop new capacities and strengthen others. The program is Proy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…This mechanism was found to be operationalised primarily through drawing on research or consultations to elicit dominant cultural values, which were then incorporated into the intervention content [51,54,94-112]. In some interventions, such as those carried out with gay men, the dominant immigrant community values on homosexuality were juxtaposed with the dominant cultural values in the mainstream gay community in the destination country, leading to interventions for Latino and Asian gay and bisexual men that addressed positive ethnic and sexual identities [94,95,97,113]. Sound or moderate evidence to support this mechanism was reported in 37 views studies indicating that ‘ consonance ’ mechanisms were also seen as critical by immigrants themselves.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This mechanism was found to be operationalised primarily through drawing on research or consultations to elicit dominant cultural values, which were then incorporated into the intervention content [51,54,94-112]. In some interventions, such as those carried out with gay men, the dominant immigrant community values on homosexuality were juxtaposed with the dominant cultural values in the mainstream gay community in the destination country, leading to interventions for Latino and Asian gay and bisexual men that addressed positive ethnic and sexual identities [94,95,97,113]. Sound or moderate evidence to support this mechanism was reported in 37 views studies indicating that ‘ consonance ’ mechanisms were also seen as critical by immigrants themselves.…”
Section: Resultsmentioning
confidence: 99%
“…There was positive feedback of ‘ understanding ’ mechanisms reported in two studies of a single intervention with Latina immigrant women in the USA [99,100] and in an intervention with Turkish and Moroccan immigrants in The Netherlands [158]. There were reports of general satisfaction or improved recruitment to, or demand for, intervention activities among programme participants in five studies that employed this adaptive mechanism [51,54,95,110,124], though this could not be attributed specifically to the use of the first language of immigrants. The evidence to support this mechanism in views studies indicated that what immigrants themselves most value is ‘closeness’ in terms of ‘shared language’ [115,120,121,125-127,129-133,140,144,147,150,165,166].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is related to informants’ concerns about improving the knowledge base of CBO staff, the services they provide, and the CBO infrastructure. It appears that meaningful collaboration asks researchers to devote more time to staff training and CBO capacity building (Clark & McLeroy, 1995; Conner, Takahashi, Ortiz, Archuleta, Muniz, & Rodriguez, 2005). If a balance is not achieved among CBO time, human resources, and the researcher’s direct involvement with a research project, it may indeed discourage CBOs from collaborating in HIV-prevention research.…”
Section: Discussionmentioning
confidence: 99%
“…Internal validity focused on whether a difference occurred that was caused by a special treatment or program; external validity was concerned with the generalizability of the effect to other groups, over different times and settings. Cook and Campbell (1979) expanded this validity formulation, and recently Shadish, Cook, and Campbell (2002) refined it further. Shadish, Cook, and Campbell specify four types of validity: internal, external, construct, and statistical conclusion.…”
mentioning
confidence: 99%